Reciprocal METTL3-PAX5 regulation in maintaining B-cell identity and promoting B-cell hyperreactivity in SLE - Yiying Yang; Ying Zhang; Shasha Xie; Ke Liu; Meidong Liu; Yisha Li; Hui Luo; Xiaoxia Zuo; Huali Zhang; Muyao Guo (Molecular Medicine)
Abstract Objective METTL3, an m6A methyltransferase, enhances germinal center responses. This study explores its role in lupus B cells and its impact on B-cell activation. Methods METTL3 and m6A levels in B cells from systemic lupus erythematosus (SLE) patients and lupus-prone mice were analyzed using m6A dot blot, RT-qPCR, western blotting, and flow cytometry. B-cell activation and differentiation were induced with lipopolysaccharide (LPS). The effects of METTL3 overexpression or inhibition on B-cell maturation were assessed in vivo. In Raji B cells, METTL3 and PAX5 knockdowns were performed to examine their regulatory relationship. EMSA and dual-luciferase assays confirmed PAX5 binding to the METTL3 promoter, while RIP and actinomycin D assays evaluated METTL3’s interaction with PAX5 mRNA. MeRIP-seq profiled m6A modifications across B-cell subsets. Results METTL3 expression and m6A levels were significantly elevated in B cells from SLE patients, with METTL3 levels positively correlating with disease activity. Elevated m6A and METTL3 levels were observed in both naïve and activated B cells but decreased markedly during differentiation into ASCs, both in vivo and in vitro. MeRIP-seq analysis identified distinct m6A methylation patterns among B-cell subsets, particularly in key transcription factors critical for B-cell activation and differentiation. METTL3 facilitated pre-B cell development in bone marrow and maintained the balance of splenic B-cell subsets in mice. Furthermore, METTL3 preserved B-cell identity and enhanced activation. Mechanistically, METTL3 bound to PAX5 mRNA, stabilizing it via m6A modification and promoting PAX5 expression. In turn, PAX5 directly bound to the METTL3 promoter, driving its expression. Conclusion The elevated expression of METTL3 in lupus B cells is linked to the maintenance of autoreactive B-cell hyperresponsiveness, contributing to the pathogenesis of SLE. The reciprocal regulation between METTL3 and PAX5 highlights a critical mechanism underlying B-cell activation and persistence in autoimmune conditions like lupus.